Chromosome imbalance, normal phenotype, and imprinting. - Bortotto, L (1990)
A duplication of the sub-bands 1q42.11 and 1q42.12 was found in a boy and his mother. The proband has short stature (around the 10th centile) but a normal phenotype and psychomotor development. His mother is also asymptomatic. We found 30 published cases of normal subjects with an imbalance of autosomal euchromatic material. In these cases the imbalance involved either only one G positive band or a G positive and a G negative band. Thus the absence of a phenotypic effect cannot always be ascribed to the deficiency in the G positive bands of coding DNA. Moreover, in some cases, the method of transmission of the chromosome abnormality was such that an imprinting effect could be postulated.